Rancang Bangun Sistem Informasi Pustaka Online Berbasis Web untuk Kampus STMIK Indonesia Banda Aceh - Zulfinar, Dara; Nurrisma; Imilda (Jurnal Sistem Komputer (SISKOM), 2023)
In the current digital era, the development of information and communication technology has had a significant impact on various aspects of life, including in the world of education. One of the important things in education is access to adequate information sources. Currently, the library system used at the STMIK Indonesia Banda Aceh campus still uses conventional methods with physical libraries, which can cause limited access, delays in obtaining information sources, as well as limitations in managing and maintaining book collections. STMIK Indonesia Banda Aceh has a library that still uses a manual recording system or bookkeeping in carrying out more and more transactions, which will certainly increase the difficulty in processing library data, not to mention errors in borrowing and returning book transactions, as well as other reporting errors. Based on the results of designing the library website system at STMIK Indonesia Banda Aceh, the results showed that the system can carry out the online loan registration process and fine notifications. The author hopes that in creating this library information system, it can help make it easier for staff and all related parties to process library data effectively and efficiently.